Formation of Local Elite Power Base in Local Politics: “The Emerging” and “The Surviving” - Haboddin, Muhtar; Afala, La Ode Machdani (UI Scholars Hub, 2023)
Many recent studies show the development of an increasingly diverse elite characterized by the emergence of a new elite and, on the other hand, the collapse of the old elite. However, these studies mainly infer democratic political change as an explanatory factor. This article takes a different standpoint to explain why some local elites collapse, survive, and emerge as new elites. Specifically, this article describes the formation of the elite resource base and its accumulation by emphasizing the perspective of social changes. Resources become the basis of power that determines the position of the elite in society and the political arena. In the data-collecting process, this study conducted interviews with several patrons and local elites accompanied by the collection of other secondary data. Our findings explain that the factor of social changes at the local level becomes the driving force that determines the emergence and collapse of the elite at the local level. The changes in the social structure of society from feudal and hierarchical to modern-competitive society have transformed the composition of the resource base of elite power in society and determined the rise and fall of elite power. In addition, the changes in social structure not only encourage the emergence of other resource bases but also opens up opportunities for the elite to accumulate them. Three critical resources determine the elite's position in Biringkassi village, namely cultural, economic, and educational resources. These three resources determine the formation and shifts of the elite in society. The study asserts that although local political changes occur within a formal-democratic framework, local communities are still tied to a power base that persists outside that framework.